Energy models for cost-optimal analysis: Development and calibration of residential reference building models for Northern Cyprus - Dakyen, Manta Marcelinus; Dagbasi, Mustafa; ozdenefe, Murat (Sage Publications Ltd, 2022)
Ambitious energy efficiency goals constitute an important roadmap towards attaining a low-carbon society. Thus, various building-related stakeholders have introduced regulations targeting the energy efficiency of buildings. However, some countries still lack such policies. This paper is an effort to help bridge this gap for Northern Cyprus, a country devoid of building energy regulations that still experiences electrical energy production and distribution challenges, principally by establishing reference residential buildings which can be the cornerstone for prospective building regulations. Statistical analysis of available building stock data was performed to determine existing residential reference buildings. Five residential reference buildings with distinct configurations that constituted over 75% floor area share of the sampled data emerged, with floor areas varying from 191 to 1006 m(2). EnergyPlus models were developed and calibrated for five residential reference buildings against yearly measured electricity consumption. Values of Mean Bias Error (MBE) and Cumulative Variation of Root Mean Squared Error CV(RMSE) between the models' energy consumption and real energy consumption on monthly based analysis varied within the following ranges: (MBE)(monthly) from -0.12% to 2.01% and CV(RMSE)(monthly) from 1.35% to 2.96%. Thermal energy required to maintain the models' setpoint temperatures for cooling and heating varied from 6,134 to 11,451 kWh/year.
Keywords: Reference buildings; Energy simulation; Manual calibration; Residential buildings; Energy efficiency; EPBD recast